Green logistics - a study of logistics sustainability part I modal shift - Ye, Lijun. (2011)
Modal shift has been the focus of transport strategies in recent years, especially for Europe where the European Union (EU) is pumping in millions as funding for modal shift projects in the region. Modal shift advocates the use of greener transportation modes like rail and shipping as alternatives for road transport. After some research, and with reference to case studies and interviews, modal shift has indeed shown to be beneficial to the environmental and society. Rail and waterborne transport have proven to be greener to the environment than road, with notably lesser air pollutants and CO2 emissions due to their energy efficiency. This in turn leads to lower negative health impacts to the society, besides the decrease in accident probability and alleviation of road congestions. Economically, in view of rising fuel prices, the energy efficiency of modal shift amounts to huge cost savings. However, the required high initial cost from its structural inelasticity poses to be a great barrier to entry for investors. Hence, there is a need for government initiatives to encourage modal shift projects, which can also be made more sustainable through the incorporation of intermodalism and other green logistics movements as a total logistics solution.